KNOWLEDGE MANAGEMENT AFFECTING EFFECTIVENESS OF SECONDARY SCHOOLS UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE 5 - Konkang, Nichapa; Dararuang, Kritsana; Supirak, Somsak (Journal for Developing the Social and Community, 2021)
Abstract The purposes of the study were: 1) To study the level of knowledge management and the level of effectiveness of the secondary schools of the Office of the Secondary Education Service Area 5, 2) To study the relationship between knowledge management and the effectiveness of secondary schools under the Office of the Secondary Education Service Area 5, 3) To study knowledge management affecting the effectiveness of secondary schools of the Secondary Education Service Area Office 5. The sample were secondary school teachers of the Secondary Education Service Area 5, total 338 people. The research tool was a questionnaire. 5-level estimation scale. With a straight value of 0.6 - 1.0 and the accuracy of 0.88. The statistics used in the research are Percentage value, mean nuance, standard deviation, correlation coefficient, and standard multiple regression analysis. The research results were found that. The correlation coefficient and the multiple linear regression were found that 1) The level of knowledge management and the level of the effectiveness of secondary schools of the Office of the Secondary Education Service Area 5 were at very high level. 2) The knowledge management correlated with the effectiveness of secondary schools of the Secondary Education Service Area Office 5 with coefficient of correlation between .159-.586 which was statistically significant at .01 3) The knowledge management of transferring and dissemination, create knowledge, analysis and knowledge mining, and knowledge storage can explain the variance or predict the effectiveness of the secondary school of the Secondary Education Service Area Office 5 by 58 percent. The forecast equations were as follows: = 0.21+ .231X5+ .260X2 + .196X4+.195X3 = .266X5+ .250X2+ .227X4+ .215X3